Corpus linguistics and translation tools for digital humanities research methods and applications - Maci, Stefania; Sala, Michele (Bloomsbury Academic, 2022)
"Presenting the digital humanities as both a domain of practice and as a set of methodological approaches to be applied to corpus linguistics and translation, chapters in this volume provide a novel and original framework to triangulate research for pursuing both scientific and educational goals within the digital humanities. They also highlight more broadly the importance of data triangulation in corpus linguistics and translation studies. Putting forward practical applications for digging into data, this book is a detailed examination of how to integrate quantitative and qualitative approaches through case studies, sample analysis and practical examples."
Keywords: Corpora (Linguistics); Language and languages -- Computer-assisted instruction; Digital humanities; Forschungsmethode; Computerlinguistik; Übersetzung; Korpus -- Linguistik; Maschinelle Übersetzung; Digital Humanities; Corpus (Linguistique); Langage et langues / Enseignement assisté par ordinateur; Sciences humaines numériques